2005
DOI: 10.1007/s10720-005-0041-9
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced transformations in Ga-Ge-S : Er films prepared by laser deposition

Abstract: Films in the Ga 2 S 3 -GeS 2 -Er 2 S 3 system are prepared through ultraviolet laser deposition. It is found that the films are characterized by the photobleaching effect whose magnitude can be as large as 120 nm. In this case, the refractive index decreases by 15%. The mechanism responsible for the revealed effect is proposed, and image recording is accomplished. LensLaser beam Substrate Target Vacuum chamber Fig. 1. Schematic diagram illustrating deposition by laser ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The schematics of experimental assembly to produce thin-film structures with the help of laser ablation with XeCl pulse exсimer laser (wavelength 308 nm, pulse time 20 ns, pulse energy 10-40 mJ) is described in the work 4 In the present work the target is represented by the set of 12 "tablets" (6 AgI tablets and 6 ZnO tablets) arranged around the moving cylinder with 20 mm diameter. Due to syncing of cylinder rotation, period and phase of laser pulse repetition, it is possible to control laser pulses hitting certain type of tablets.…”
Section: Methodsmentioning
confidence: 99%
“…The schematics of experimental assembly to produce thin-film structures with the help of laser ablation with XeCl pulse exсimer laser (wavelength 308 nm, pulse time 20 ns, pulse energy 10-40 mJ) is described in the work 4 In the present work the target is represented by the set of 12 "tablets" (6 AgI tablets and 6 ZnO tablets) arranged around the moving cylinder with 20 mm diameter. Due to syncing of cylinder rotation, period and phase of laser pulse repetition, it is possible to control laser pulses hitting certain type of tablets.…”
Section: Methodsmentioning
confidence: 99%
“…The films thus prepared have a high adhesion to the surface of the glass substrate. According to [9,10], this method makes it possible to prepare films with a complex chemical composition coinciding with the target composition. The switching of the laser beam from one target to another target with simultaneous counting of laser pulses in order to control the thickness of evaporated layers allowed us to produce virtually any multilayer configurations.…”
Section: Sample Preparations and Experimental Techniquementioning
confidence: 99%
“…The conditions and technique used for deposition of films were described in our previous paper [4]. In order to improve the homogeneity of the films, we used a special crown with twelve sites that were arranged at different angles and intended to fix initial glass samples (targets) [5].…”
Section: Sample Preparation and Experimental Techniquementioning
confidence: 99%
“…In our earlier works [3,4], it was demonstrated that, for Ga-Ge-S : Er films prepared by laser deposition, the photoinduced shift in the fundamental absorption edge toward the short-wavelength range can be as large as 120 nm and is accompanied by a change in the refractive index.…”
Section: Introductionmentioning
confidence: 99%